A community for students.
Here's the question you clicked on:
 0 viewing
dtan5457
 one year ago
Factor this
dtan5457
 one year ago
Factor this

This Question is Closed

dtan5457
 one year ago
Best ResponseYou've already chosen the best response.0\[a^{2n+1}+b^{2n+1}+a^{2n}b^{2n}+ab\]

dtan5457
 one year ago
Best ResponseYou've already chosen the best response.0@jdoe0001 @jim_thompson5910 @Loser66

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0\(a^{2n+1}+b^{2n+1}+a^{2n}b^{2n}+ab\qquad \begin{cases} a^{2n+1}=a^{2n}\cdot a^1\implies a^{2n}a\\ b^{2n+1}=b^{2n}\cdot b^1\implies b^{2n}b \end{cases}\qquad thus \\ \quad \\ a^{2n}a+b^{2n}b+a^{2n}b^{2n}+ab \\ \quad \\ (a^{2n}a+ab)+(b^{2n}b+a^{2n}b^{2n})\impliedby \textit{any common factors?}\)

dtan5457
 one year ago
Best ResponseYou've already chosen the best response.0when you have a^2n(a), that wouldn't be a^4n?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0anyhow \(a^{2n+1}+b^{2n+1}+a^{2n}b^{2n}+ab\qquad \begin{cases} a^{2n+1}=a^{2n}\cdot a^1\implies a^{2n}a\\ b^{2n+1}=b^{2n}\cdot b^1\implies b^{2n}b \end{cases}\qquad thus \\ \quad \\ a^{2n}a+b^{2n}b+a^{2n}b^{2n}+ab \\ \quad \\ (a^{2n}a+ab)+(b^{2n}b+a^{2n}b^{2n}) \\ \quad \\ a({\color{brown}{ a^{2n}+b}})+b^{2n}( b+a^{2n})\implies a({\color{brown}{ a^{2n}+b}})+b^{2n}({\color{brown}{ a^{2n}+b }} )\) see any more common factors?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0\(\large { a^n\cdot a^m\implies a^{n+m} \\ \quad \\ a^{2n+1}=a^{2n}\cdot a^1\implies a^{2n}a }\)

dtan5457
 one year ago
Best ResponseYou've already chosen the best response.0oh well, then your final answer should be (a^2n+b)(a+b^2n)?

dtan5457
 one year ago
Best ResponseYou've already chosen the best response.0that a^2n(a) was confusing for me cause i thought it meant a^2(2n)=a^4n, im just reading it wrong i guess

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0well... \(\large \begin{cases} a^{2n+1}=a^{2n}\cdot a^1\implies a^{2n}\cdot a\implies a^{2n}a\\ b^{2n+1}=b^{2n}\cdot b^1\implies b^{2n}\cdot b\implies b^{2n}b \end{cases}\)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.